144k views
4 votes
3/4+ (1/3 ➗1/6)- (-1/2)=___

1 3/4

2 1/4

3/4

3 1/4

1 Answer

4 votes

STEP 1: (1/3 : 1/6) = 2/1 = 2

STEP 2: 3/4 + 2 = 11/4 = 2 3/4 = 2.75

STEP 3: 2.75 (-1/2) = -11/8 = -1 3/8 = -1.375

(1) Divide: 1/3 : 1/6 = 1/3 · 6/1 = 1 · 6/3 · 1 = 6/3 = 3 · 2 /3 · 1 = 2

(2)Add: 3/4 + the result of step No. 1 = 3/4 + 2 = 3/4 + 2/1 = 3/4 + 2 · 4/1 · 4 = 3/4 + 8/4 = 3 + 8/4 = 11/4

(3) Subtract: the result of step No. 2 - (-1/2) = 11/4 - (-1/2) = 11/4 - (-1) · 2/2 · 2 = 11/4 - (-2/4) = 11 - (-2)/4 = 13/4

Therefor your answer is A 13/4 OR 1 and 3/4: )

Hope this helps!

Sorry for all the steps but those steps will help you!

-Hailey: )

(nothing is copied or pasted!!!!!)

User Ahd Radwan
by
6.2k points